Critical Thinking Skills Profile in Plant Reproduction Material at the Elementary School Level - Widyalistyorini, Dian; Suprapto, Nadi; Suryanti (Jurnal Elementaria Edukasia, 2024)
As the components of the Pancasila Student Profile change, a key objective of twenty-first-century education is to foster critical thinking skills. The primary aim of this study is to outline critical thinking skills in science education centered around Plant Reproduction materials at the elementary school level. A quantitative descriptive approach is employed, involving seventeen sixth-grade students from SD Negeri Ceweng as participants. The research tool used is a two-tier multiple-choice assessment. The assessment designed based on six indicators of critical thinking skills: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The finding revealed that students scored 37.05% (low category) in Interpretation, 57.65% (medium category) in Analysis, 79.4% (high category) in Evaluation, 73.5% (high category) in Inference, 57.65% (medium category) in Explanation, and 34.15% (low category) in Self-Regulation. In general, the students' average score for critical thinking was 56.57%, indicating a medium or relatively good level of critical thinking.